2013
DOI: 10.1097/eja.0b013e3283625039
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of four facial muscles, orbicularis oculi, corrugator supercilii, masseter or mylohyoid, as best predictor of good conditions for intubation

Abstract: IRB File No.: HYUH 2012-07-009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The depth of anesthesia is known to influence intubating conditions: therefore, all variables of anesthesia were standardised. The size of the groups was similar to those in other studies dealing with this topic [ 10 , 11 , 15 ], and the rate of excellent intubating conditions (73%) was comparable to the results of other authors observing 70 to 80% [ 16 , 17 ]. However, we were not able to find differences between both measurement sites with regard to intubating conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The depth of anesthesia is known to influence intubating conditions: therefore, all variables of anesthesia were standardised. The size of the groups was similar to those in other studies dealing with this topic [ 10 , 11 , 15 ], and the rate of excellent intubating conditions (73%) was comparable to the results of other authors observing 70 to 80% [ 16 , 17 ]. However, we were not able to find differences between both measurement sites with regard to intubating conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The authors observed best intubating conditions if the adductor pollicis muscle was chosen to predict onset of the neuromuscular block; however, with the longest delay between start of anesthesia and tracheal intubation. In a second study, they compared orbicularis oculi, corrugator supercilii, masseter and mylohyoid muscles with each other [ 11 ]. Again, best intubating conditions were observed at the measurement sites with the longest delay between induction and complete neuromuscular block (mylohyoid muscle).…”
Section: Discussionmentioning
confidence: 99%
“…Intubation conditions are related more closely to the degree and time of onset of NMB in the laryngeal adductors, diaphragm, and masseter muscles than in the adductor pollicis muscle ( 15 ). Monitoring NMB at different muscles may provide additional information that can be used to effectively prevent hemodynamic responses to intubation despite good or excellent intubation conditions ( 15 - 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with nociceptive stimulation (laryngoscopy), the increase in BIS in patients who received rocuronium (0.6 mg/kg) was significantly lower than in patients who did not (saline) ( 18 ). We performed intubation when the TOF ratio reached zero to prevent the sympathetic response to stimulus before intubation and the large interindividual variation in neuromuscular depression that can occur after administration of NMB agents ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…En estudios comparando la monitorización de varios grupos musculares se obtuvo el menor tiempo en alcanzar el bloqueo máximo con el OO 75 , aunque las condiciones de intubación no son siempre aceptables 76 . Monitorizando el músculo AP se obtiene condiciones de intubación excelentes, aunque con mayor retraso en alcanzar el bloqueo máximo tras la administración de un bolo de relajante muscular.…”
Section: Fonomiografía (Pmg)unclassified